Treatment patterns and intensification within 5 year of follow-up of the first-line anti-TNFα used for the treatment of IBD: Results from the VERNE study. Issue 1 (January 2022) - Bastida, G.; Marín-Jiménez, I.; Forés, A.; García-Planella, E.; Argüelles-Arias, F.; Tagarro, I.; Fernandez-Nistal, A.; Montoto, C.; Aparicio, J.; Aguas, M.; Santos-Fernández, J.; Boscá-Watts, M.M.; et al.
Abstract: Background: Anti-TNFα represent one of the main treatment approaches for the management of inflammatory bowel diseases (IBD). Therefore, the evaluation of their treatment patterns over time provides valuable insights about the clinical value of therapies and associated costs. Aims: To assess the treatment patterns with the first anti-TNFα in IBD. Methods: Retrospective, observational study. Results: 310 IBD patients were analyzed along a 5-year follow-up period. 56.2% of Crohn's disease (CD) patients started with adalimumab (ADA), while 43.8% started with infliximab (IFX). 12.9% of ulcerative colitis (UC) patients initiated with ADA, while 87.1% initiated with IFX. Treatment intensification was required in 28.9% of CD and 37.1% of UC patients. Median time to treatment intensification was shorter in UC than in CD (5.3 vs. 14.3 months; p  = 0.028). Treatment discontinuation due to reasons other than remission were observed in 40.7% of CD and 40.5% of UC patients, although, in UC patients there was a trend to lower discontinuation rates with IFX (36.6%) than with ADA (66.7%). Loss of response accounted for approximately one-third of discontinuations, in both CD and UC. Conclusions: Around one-third of IBD biologic-naive patients treated with an anti-TNFα required treatment intensification (earlier in UC) and around 40% discontinued the anti-TNFα due to inappropriate disease control.